The study outcome of bouquet technique for the management of displaced boxer’s fracture - Kumar, Ranjith; Saini, Narender; D. S., Meena; Bains, Sukhandeep Singh; Kumar, Ajith (International Journal of Research in Orthopaedics, 2023)
Background: Fifth metacarpal neck fracture is also called Boxer’s fracture. Most commonly occurs due to aggression behaviour that result in punch on a wall with a clenched first. If there is a displacement of boxer’s fracture more than 500 then it has to be managed operatively. We here present the outcome of bouquet technique that we used to operate the 80 cases of 5th metacarpal neck fracture. Methods: We studied and did follow up of the 80, 5th metacarpal neck fracture that managed by bouquet technique. Clinical and radiological assessment was done at 4weeks and 6 weeks and 12 weeks. Total active motion, radiography and complication were noted. Results: Out of 80 patients that were studied 72 got excellent results and 8 got fair results. Whereas one patient got infection and 2 got adventitious bursitis at the entry site which requires k wire removal. Conclusions: The technique of antegrade intramedullary 3 kirschners wire in management of 5th metacarpal neck fracture is safe, simple, soft tissue sparing, minimally invasive technique with excellent functional and cosmetic outcome with minimal complications.